The jurisprudence of family building in the thought of Sheikh Muhammad al-Khal - Sharif, Dr. Baqi Karim; Mahmoud, L. Dr. Omar Juma (Sulaimani Journal for Humanities, 2023)
Sheikh Muhammad al-Khal was a distinguished scholar, a gifted writer, a reformist researcher, and a sincere and successful judge in the field of law, addressing the problems facing society, including individuals, families, and groups. This is not surprising, as he was among the first scholars in Iraqi Kurdistan to join the reform movement led by the great reformer Jamal al-Din al-Afghani, Sheikh Muhammad Abduh, and Sheikh Muhammad Rashid Rida—may God have mercy on them—in Egypt at that time. For this reason, he—may God have mercy on him—focused in his exegesis, writings, and articles on issues that contribute to building a just society in all aspects of life: intellectual, doctrinal, social, economic, and political. Among the issues Sheikh Muhammad al-Khal addressed was the jurisprudence of family building, which is truly the cornerstone of building a just society. The study addresses family jurisprudence by defining the family, outlining its foundations, and examining the challenges it faces. It then proposes solutions based on the author's unique methodology and reformist thought, characterized by comprehensiveness, moderation, independence, and a balance between tradition and modernity, while preserving the distinctive features and characteristics of Kurdish society. To highlight the contributions of this eminent scholar, wise judge, and innovative researcher, the two researchers have chosen the aforementioned title for their paper submitted to your esteemed conference.